Novel Bio-Logging Tool for Studying Fine-Scale Behaviors of Marine Turtles in Response to Sound - Tyson, Reny B.; Piniak, Wendy E. D.; Domit, Camila; Mann, David; Hall, Michael; Nowacek, Douglas P.; Fuentes, Mariana M. P. B. (Frontiers in Marine Science, 2017)
Increases in the spatial scale and intensity of activities that produce marine anthropogenic sound highlight the importance of understanding the impacts and effects of sound on threatened species such as marine turtles. Marine turtles detect and behaviorally respond to low-frequency sounds, however few studies have directly examined their behavioral responses to specific types or intensities of anthropogenic or natural sounds. Recent advances in the development of bio-logging tools, which combine acoustic and fine-scale movement measurements, have allowed for evaluations of animal responses to sound. Here, we describe these tools and present a case study demonstrating the potential application of a newly developed technology (ROTAG, Loggerhead Instruments, Inc.) to examine behavioral responses of freely swimming marine turtles to sound. The ROTAG incorporates a three-axis accelerometer, gyroscope, and magnetometer to record the turtle’s pitch, roll, and heading; a pressure sensor to record turtle depth; a hydrophone to record the turtle’s received underwater acoustic sound field; a temperature gauge; and two VHF radio telemetry transmitters and antennas for tag and turtle tracking. Tags can be programmed to automatically release via a timed corrodible link several hours or days after deployment. We describe an example of the data collected with these tags and present a case study of a successful ROTAG deployment on a juvenile green turtle (Chelonia mydas) in the Paranaguá Estuary Complex, Brazil. The tag was deployed for 221 minutes, during which several vessels passed closely (<2km) by the turtle. The concurrent movement and acoustic data collected by the ROTAG were examined during these times to determine if the turtle responded to these anthropogenic sound sources. While fine-scale behavioral responses were not apparent (second-by-second), the turtle did appear to perform dives during which it remained still on or near the sea floor during several of the vessel passes. This case study provides proof of concept that ROTAGs can successfully be applied to free-ranging marine turtles to examine their behavioral response to sound. Finally, we discuss the broad applications that these tools have to study the fine-scale behaviors of marine turtles and highlight their use to aid in marine turtle conservation and management.